The Parable of the Auctioneer: Complexity in Paul R. Milgrom’sDiscovering Prices - Kominers, Scott Duke; Teytelboym, Alexander (Journal of Economic Literature, 2020)
Designing marketplaces in complex settings requires both novel economic theory and real-world engineering, often drawing upon ideas from fields such as computer science and operations research. In Discovering Prices: Auction Design in Markets with Complex Constraints, Milgrom (2017) explains the theory and design of the United States’ “incentive auction” that reallocated wireless spectrum licenses from television broadcasters to telecoms. Milgrom’s account teaches us how economic designers can grapple with complexity both in theory and in practice. Along the way, we come to understand several different types of complexity that can arise in marketplace design. (JEL D43, D44, D47, L96, L98)